2005
DOI: 10.1037/1082-989x.10.4.371
|View full text |Cite
|
Sign up to set email alerts
|

An Abductive Theory of Scientific Method.

Abstract: A broad theory of scientific method is sketched that has particular relevance for the behavioral sciences. This theory of method assembles a complex of specific strategies and methods that are used in the detection of empirical phenomena and the subsequent construction of explanatory theories. A characterization of the nature of phenomena is given, and the process of their detection is briefly described in terms of a multistage model of data analysis. The construction of explanatory theories is shown to involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
207
0
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(224 citation statements)
references
References 64 publications
3
207
0
14
Order By: Relevance
“…Another limitation is the lack of developed theory guiding research on word use and personality. However, Haig (2005) observed that for the past 150 years, science has been dominated by the idea that theory should precede empirical observation (the "hypothetico-deductive method"). He argued that this is a rather narrow of view of the scientific process and proposed an alternative called the "abductive theory of scientific method."…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the lack of developed theory guiding research on word use and personality. However, Haig (2005) observed that for the past 150 years, science has been dominated by the idea that theory should precede empirical observation (the "hypothetico-deductive method"). He argued that this is a rather narrow of view of the scientific process and proposed an alternative called the "abductive theory of scientific method."…”
Section: Discussionmentioning
confidence: 99%
“…This theorization was guided by the existing empirical evidence (Ziakas, 2007), rather than limited by it, since more data are needed to be collected through future research in order to test, substantiate and generalize the suggested theoretical insights. Thus, the theoretical approach employed in this paper seeks to explain the phenomenon of event portfolio planning and leveraging by drawing inferences to the best explanation (Haig, 1995). In short, the proposed conceptual frameworks of this paper are ever-developing entities, and not perfected products, as they were generated and appraised by an abductive reasoning process of a realist and explanatory inferentialism (Haig, 1995) that focuses on understanding common causes and patterns by making inference to the best explanation (Lipton, 2001).…”
Section: Event Portfolio Planning and Leveragingmentioning
confidence: 99%
“…The interview data were analysed using the constant comparison method (Haig, 1996). This approach aims to inductively detect themes and patterns in the data, and develop concepts out of these patterns.…”
Section: Insert Figure 3 About Herementioning
confidence: 99%